Procedure for culturing non sporulating fungi at microscale level / Maisarah Mustafa - Mustafa, Maisarah (2013)
Filamentous fungi provide unique compounds as a source for drug discovery. Conventional screening method is not practical to screen the bioactive compounds produced by thousands fungi. In order to increase the output, there is need to decrease the scale and increase the output. Using in-house MECSUS protocol with slight modification, a procedure for culturing non-sporulating fungi at microscale level using microtiter plate was developed by studying 11 fungi from Atta-ur Rahman Institute's collection. The procedure consists of four major stages including growth study, culturing process, solid phase extraction process and HPLC chromatographic screening, profiling and analysis. Eight fungi were characterized as fast growing fungi while three fungi were medium growing fungi. The fungal inoculum preparation was established based on growth kinetic study by preparing mycelium suspension. The fungal myceliurn suspensions were cultured in rnicrotiter plate and incubated according to growth study. The fungi were extracted using parallel solid phase extraction based on in-house MECSUS protocol. The fungal extracts were analyzed using HPLC. The profiling showed consistency and reproducible results. The procedure was found effective and reliable. The procedure will be included as the part of in-house MECSUS protocol.